2015
DOI: 10.1001/jama.2015.8897
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Dialysis Facility Referral for Kidney Transplantation Among Patients With End-Stage Renal Disease in Georgia

Abstract: IMPORTANCE Dialysis facilities in the United States are required to educate patients with end-stage renal disease about all treatment options, including kidney transplantation. Patients receiving dialysis typically require a referral for kidney transplant evaluation at a transplant center from a dialysis facility to start the transplantation process, but the proportion of patients referred for transplantation is unknown.OBJECTIVE To describe variation in dialysis facility-level referral for kidney transplant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(145 citation statements)
references
References 34 publications
8
136
1
Order By: Relevance
“…Patient-level data on transplant referrals between 2008 and 2012 were collected from all three transplant centers in the state of Georgia (Emory Transplant Center [Atlanta], Augusta University Medical Center [Augusta], and Piedmont Transplant Institute [Atlanta]) as previously described (3,16). ESRD Network 6 served as the data coordinating center and linked patient-level referral data with dialysis facility data by unique provider number.…”
Section: Data Sources and Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient-level data on transplant referrals between 2008 and 2012 were collected from all three transplant centers in the state of Georgia (Emory Transplant Center [Atlanta], Augusta University Medical Center [Augusta], and Piedmont Transplant Institute [Atlanta]) as previously described (3,16). ESRD Network 6 served as the data coordinating center and linked patient-level referral data with dialysis facility data by unique provider number.…”
Section: Data Sources and Study Populationmentioning
confidence: 99%
“…Although national transplant referral data are unavailable, we recently collected patient referral data from all Georgia transplant centers as part of the Reducing Disparities in Access to Kidney Transplantation Community Study, and an extension of this data collection in other states is underway (13). The few studies that have examined transplant performance using transplant referral have used facility-level absolute referral rate to measure facility performance (3,14,15). In a recent study, we examined whether absolute facility referral was associated with other quality metrics within dialysis facilities and found that referral was not associated with other metrics, such as anemia management, morbidity, or mortality, and although referral was associated with waitlisting and transplantation, it was not entirely correspondent with these other measures of transplant access.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[1] Inadequate education may particularly impact patients with lower socioeconomic status or members of racial/ethnic minorities, contributing to lower rates of referral and transplant listing [2][3][4][5][6]. In addition, patients may choose to reject high KDPI and PHS increased risk organs that are expected to provide benefit out of fear or incomplete understanding of the relative risk of death on dialysis.…”
Section: Accepted Articlementioning
confidence: 99%
“…Finding the appropriate number of patients for a navigator may vary from center to center, and a lower navigator-to-patient ratio may be most beneficial in improving access to care. For example, we have previously reported that a lower social worker-to-patient ratio is associated with higher transplant referral in our state (41). Although upfront costs to the transplant center may be an issue, targeting the intervention to those patients most in need could help control transplant center costs.…”
Section: Discussionmentioning
confidence: 93%